Some recent Australian research on workplace learning and training - Andrew Gonczi (Adult Education Research Conference, 1996)
This paper describes two recent Australian projects, which examined the learning of generic competencies in industry settings and considered possible ways of enhancing these competencies through a variety of training approaches.